Dampak Penerapan Kurikulum Merdeka Belajar di Sekolah Islam: (Studi Kasus di Mi Maarif Giriloyo 1 Imogiri Bantul) - Mahmudah, Iib; Pranajati, Nindya Rachman (QuranicEdu: Journal of Islamic Education, 2024)
This research explores how the Independent Learning Curriculum in grade IV is implemented and how this encourages the emergence of various forms of creativity in students in grade IV at MI Maarif Giriloyo 1 Imogiri Bantul. The method used in this research is field research with a qualitative approach. Data collection techniques in this research used observation, interview, and documentation techniques. The research results show: first, the application of the Independent Learning Curriculum to the creativity of grade IV students, namely the stages in the implementation of the Independent Curriculum learning in the form of the planning stage, the implementation stage, and the assessment stage. Second, a lot of creativity is formed in fourth grade students, namely creativity of ideas (such as asking questions, basic concepts and experimenting), creativity of ideas (such as designing experiments and detailed guides of ideas), and creativity of products (such as piggy banks, posters, framed batik writing, tote bags with ecoprints, and jumput batik on clothes).